Determination of (-)-epigallocatechin-3-gallate octaacetate and its metabolites in plasma of rats for pharmacokinetic study by ultra-performance-liquid-chromatography coupled to quadrupole-time-of-flight-mass-spectrometry - Chu, Kai On; Man, Gene Chi Wai; Hung, Sze Wan; Chan, Tak Hang; Lee, Wai Yip Thomas; Chan, Kwok Ping; Pang, Chi Pui; Wang, Chi Chiu (Frontiers in Pharmacology, 2022)
Graphical Abstract